2015
DOI: 10.1152/jn.00561.2014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of GABAergic and cholinergic neurons in perinuclear zone of mouse supraoptic nucleus

Abstract: The perinuclear zone (PNZ) of the supraoptic nucleus (SON) contains some GABAergic and cholinergic neurons thought to innervate the SON proper. In mice expressing enhanced green fluorescent protein (eGFP) in association with glutamate decarboxylase (GAD)65 we found an abundance of GAD65-eGFP neurons in the PNZ, whereas in mice expressing GAD67-eGFP, there were few labeled PNZ neurons. In mice expressing choline acetyltransferase (ChAT)-eGFP, large, brightly fluorescent and small, dimly fluorescent ChAT-eGFP ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Of relevance, several studies have used either the AT2R antagonist, PD123319, or AT2R knockout mice to demonstrate that, at the doses used in the present study, C21 exerts AT2R-specific effects (47)(48)(49)(50). Initial patch-clamp electrophysiological studies revealed that AT2R-expressing neurons in the peri-PVN shared similar general electrophysiological properties to previously described hypothalamic interneurons, including GABAergic ones, such as the expression of a rebound LTS and a mostly linear current/voltage relationship (51,52). Importantly, we found that activation of AT2R with the selective agonist C21 excites AT2R-eGFP neurons in the peri-PVN area, evoking and/or increasing their firing discharge.…”
Section: Discussionmentioning
confidence: 58%
“…Of relevance, several studies have used either the AT2R antagonist, PD123319, or AT2R knockout mice to demonstrate that, at the doses used in the present study, C21 exerts AT2R-specific effects (47)(48)(49)(50). Initial patch-clamp electrophysiological studies revealed that AT2R-expressing neurons in the peri-PVN shared similar general electrophysiological properties to previously described hypothalamic interneurons, including GABAergic ones, such as the expression of a rebound LTS and a mostly linear current/voltage relationship (51,52). Importantly, we found that activation of AT2R with the selective agonist C21 excites AT2R-eGFP neurons in the peri-PVN area, evoking and/or increasing their firing discharge.…”
Section: Discussionmentioning
confidence: 58%
“…This suggests that, in the experimental conditions, apamin also had presynaptic actions, either reducing excitatory input or increasing inhibitory input. The latter is more likely because the actions of apamin would be generally expected to increase neuronal excitability, increasing spike rate as is observed in vitro (34), and supraoptic neurones receive an extensive inhibitory input from GABA neurones in the perinuclear zone immediately adjacent to the supraoptic nucleus (35,36).…”
Section: Discussionmentioning
confidence: 96%
“…The I A underlies the prominent transient outward rectification (TOR) that delays spike activation in magnocellular PVN and SON neurones when depolarised from hyperpolarised membrane potentials, contributes to spike repolarisation, and likely plays a significant role in somatic and terminal spike broadening (ie, which facilitates Ca 2+ influx) via its activity‐dependent inactivation. The strong presence of TOR in the magnocellular neurones distinguishes them from many surrounding parvocellular neurones in the PVN and SON . Most SON neurones are immunopositive for an A‐type channel subunit, KV4.2 .…”
Section: Properties Of Identified Ot and Vp Neuronesmentioning
confidence: 99%